El public compliance en el Perú. Estado de la cuestión y desafíos hacia la construcción de una agencia Anticorrupción - Pereyra Villar, Tania (2024)
This research examines the anti-bribery agencies of Italy, Spain and Peru. The study covers two key international regulatory frameworks in the fight against bribery: the Inter-American Convention and the United Nations Convention. As a main contribution, a centralized and specialized body to combat this crime is proposed, based on a mixed model. This approach seeks to integrate international best practices, adapting them to the realities of each country. Likewise, a critical assessment is made of the continuous implementation of public compliance in Peruvian legislation, evaluating its progress in various institutions of public administration. These aspects are contrasted with the proposed model, highlighting its importance in the current context.